Assessment instruments used for the self-report of pain by hospitalized stroke patients with communication problems: a scoping review protocol - Mandysova, Petra; Klugar, Miloslav; de Vries, Neeltje J Carolien; Matějková, Iryna (JBI evidence synthesis, 2020)
OBJECTIVE: The objective of this scoping review is to systematically identify assessment instruments that are used for the self-report of pain by hospitalized stroke patients with communication problems. INTRODUCTION: To the best of the authors' knowledge, there are no existing instruments specifically dedicated to measuring pain in stroke patients with communication problems. Pain measurement instruments currently in use may complicate pain assessment in these patients. Additionally, there is a lack of consensus regarding these patients' ability to self-report pain using existing pain instruments. INCLUSION CRITERIA: The review will consider studies that focus on hospitalized adults where at least one subgroup has been diagnosed with stroke as well as associated communication problems attributable to a stroke. The concept of interest is assessment instruments used for the self-report of pain by these patients. The scoping review will include systematic reviews, quantitative studies of any design, and mixed methods studies. METHODS: The search will occur in three phases: an initial limited search, a full search, and a screening of the reference lists of all the included articles. The key information sources include: PubMed, CINAHL, Nursing@Ovid, the Cochrane Library, Web of Science, Scopus, and Embase. All identified citations will be uploaded to a reference management program, and the titles and abstracts screened. Full texts of studies potentially meeting the inclusion criteria will be assessed in detail, with relevant data extracted and reported in tabular as well as descriptive format that aligns with the objectives and scope of this review.
Keywords: cévní mozková příhoda; dospělí; Communication; komunikace; Pain; bolest; scoping review jako téma; Scoping Reviews As Topic; lidé; zpráva o sobě; Self Report; Stroke; Adult; Humans